THE INFLUENCE OF HEALTH EDUCATION ABOUT THE DANGERS OF SMOKING ON ADOLESCENT KNOWLEDGE - Kapugu, Christine; Bobaya, Janbonsel; Warouw, Herman J. (POLITEKNIK KESEHATAN KEMENTERIAN KESEHATAN MANADO, 2022)
Background: The increasing number of smokers in adolescents increases the risk of non-communicable diseases in adolescents, namely lung cancer, kidney cancer, cervical cancer and pregnancy disorders. Low knowledge can lead to ignorance due to smoking on the body. There are various methods used and the number of respondents varies with the results of 9 journals showing an increase in adolescent knowledge. Objective: namely to determine the influence of health education about the dangers of smoking on adolescent knowledge. Method: This type of research uses literature review research or theoretical review, namely by collecting journals or books and analyzing the results of the research. In order to obtain appropriate data, researchers searched National and International journals through 3 databases, namely Scopus, Google Scholar and Sage Journal with publication years 2010-2020 and researchers used 9 journals for literature review research. Results: Provision of health education increases adolescent knowledge about the dangers of smoking. Suggestion: You can look for more journal or book references so you can complete information related to the influence of health education about the dangers of smoking on teenagers' knowledge. Keywords: The dangers of smoking, education, education, cigarette, tobacco